Recycling kinetic energy from speed bump to generate electricity - Atan, Farraniza (2013)
Speed Bump one of the safety devices that use for the road. Even though it have the ability to make people reduce speed, most of the road users have a negative perception with the speed bump because it can cause damage to the car and sometimes can cause danger to the users if it not use with the right way. A system called electricity generating speed bump will be developed to change people negative perception about speed bump by expanding the speed bump function to be a source of current. This system is a combination of mechanical part that contact with speed bumps. The combination then use by generator to produce electricity. Mechanical part then consists of gear combinations, ramp and shaft. The current produced by the generator is stored in batteries to be use of the equipment. This system involved the knowledge of the generator function with Faraday’s Law concept, gear ratio, generator rotating rate and also the charging process. Analysis done to know the effectiveness of this system to be used in the real world. The analysis done with two parameters which are number of vehicle hit speed and weight applies to speed bump. From the two parameters, the ability of this system to produce output can be known. Since this system was developed with the small ratio, calculation needs to be done to know the ability of this system in huge scale which is applied in the real world. This system will be applied in low vehicle speed and high number of users. Thus, this effective system not only use for the safety element in the road but also contribute to electricity supply.